2019
DOI: 10.1073/pnas.1913741116
|View full text |Cite
|
Sign up to set email alerts
|

Corpora amylaceaact as containers that remove waste products from the brain

Abstract: Corpora amylacea(CA) in the human brain are granular bodies formed by polyglucosan aggregates that amass waste products of different origins. They are generated by astrocytes, mainly during aging and neurodegenerative conditions, and are located predominantly in periventricular and subpial regions. This study shows that CA are released from these regions to the cerebrospinal fluid and are present in the cervical lymph nodes, into which cerebrospinal fluid drains through the meningeal lymphatic system. We also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
74
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(77 citation statements)
references
References 41 publications
3
74
0
Order By: Relevance
“…Corpora amylacea are reportedly composed of glycoproteins and play an important role in the protective and clearing mechanism in the brain, prostate, lung, and muscle 3‐6,11‐18 . The staining pattern in our case is consistent with a glycoprotein component (possibly predominantly polyglucosan and a minor component of protein).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Corpora amylacea are reportedly composed of glycoproteins and play an important role in the protective and clearing mechanism in the brain, prostate, lung, and muscle 3‐6,11‐18 . The staining pattern in our case is consistent with a glycoprotein component (possibly predominantly polyglucosan and a minor component of protein).…”
Section: Discussionsupporting
confidence: 69%
“…They also contain ubiquitin and p62 associated with cleaning of waste substances, as well as glycogen synthase, an enzyme for polyglucosan formation. Based on the identification of various components it is thought that corpora amylacea play a role in lysosomal degradation, entrapment of damaged and non‐degradable material, demonstrating a protective and cleaning mechanism in the brain 12‐16 . In addition, fungal and bacterial polypeptides besides human proteins are identified in corpora amylacea, thus suggesting a role of scavenging cellular debris triggered by microbial infections 17 .…”
Section: Discussionmentioning
confidence: 99%
“…The appearance of these granules coincides with cognitive impairments in hAβ-KI mice, suggesting that the neurodegenerative process starts relatively early in this model. Of note, PAS granules have been described in human brains (originally by Purkinje, known as Corpora Amylacea (CA)), and their presence is increased in AD cases as well as other degenerative conditions 40 42 . A recent study showed that CA accumulate at the same locations in the human brain as we describe in the hAβ-KI mice, and represent an important mechanism for waste clearance from the brain parenchyma to the cerebrospinal fluid (CSF), then to the meninges and cervical lymph nodes 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Of note, PAS granules have been described in human brains (originally by Purkinje, known as Corpora Amylacea (CA)), and their presence is increased in AD cases as well as other degenerative conditions 40 42 . A recent study showed that CA accumulate at the same locations in the human brain as we describe in the hAβ-KI mice, and represent an important mechanism for waste clearance from the brain parenchyma to the cerebrospinal fluid (CSF), then to the meninges and cervical lymph nodes 42 . The build-up of CA (OC+/PAS granules) may indicate that such waste clearance mechanisms are being impaired, or overloaded or both, and could be an early stage in AD pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…However, in this case neuronal subtypes in the medullary reticular formation appeared largely preserved, verified by immunohistochemistry, but neuronal PGB inclusions were noted with a similar anatomical distribution. PGBs, which have also historically been termed ‘Bielchowsky bodies’, differ in shape, cellular and regional distribution to Lafora disease (associated with progressive myoclonic epilepsy) [9] corpora amylacea (present in astroglia) [10] glycogen storage diseases and other rarer adult polyglucosan disorders [11] , [12] . PGBs have been recognised in the context of long-standing cerebral palsy due to hypoxic-ischaemic perinatal injury, but usually involving the pallidum with rare reports of PGBs occurring in the brainstem [13] including one case report of a patient with drug-resistant epilepsy and a nocturnal sudden death [14] .…”
Section: Discussionmentioning
confidence: 99%